Efficient Solution Approach to Maximum Flow Evacuation Planning Problem without Flow Conservation Aspect - Bhandari, Phanindra Prasad; Khadka, Shree Ram (Journal of the Institute of Engineering, 2018)
An attempt of shifting as more people as possible and/or their logistics from a dangerous place to a safer place is an evacuation planning problem. Such problems modeled on network have been extensively studied and the various efficient solution procedures have been established. The solution strategies for these problems are based on source-sink path augmentation and the flow function satisfies the flow conservation at each intermediate node. Besides this, the network flow problem in which flow may not be conserved at node necessarily could also be used to model the evacuation planning problem. This paper proposes a model for maximum flow evacuation planning problem on a single-source-single-sink static network with integral arc capacities with holding capability of evacuees in the temporary shelter at intermediate nodes and extends the model into the dynamic case. Journal of the Institute of Engineering, 2017, 13(1): 108-116